The Application of Sharia Economic Principles: A Perspective on Educational Management in Community Skill Development - Ghufron, Moh. Idil; Vernanda, Zhely (Al-Qalam Institue, 2025)
This study aims to explore the application of Sharia economic principles in fish besek craft production in Bukor Village, to improve product quality, competitiveness, and the well-being of craftsmen. The implementation of Sharia economics, emphasizing justice, transparency, and blessings, can enhance product competitiveness. The research uses a qualitative phenomenological approach, involving interviews, observations, and documentation. Data analysis was performed using Miles and Huberman’s technique and SWOT matrix. The findings show that besek production emphasizes honesty and environmental friendliness, with strengths in local values and high market opportunities, but facing challenges in capital, innovation, and regeneration. This study suggests empowering traditional MSMEs through Sharia economics and contributes to the development of local community-based economic literature. Implications for educational management include the importance of developing Sharia economics-based skills in entrepreneurship curricula to empower communities and create sustainable jobs.